254 Markers of Neurodegeneration Associate with Worse Performance of Complex Daily Tasks - Audrey A. Keleman; Rebecca M. Bollinger; Beau M. Ances; Susan L. Stark (Journal of Clinical and Translational Science, 2022)
OBJECTIVES/GOALS: In preclinical Alzheimer disease (AD), biomarkers such as amyloid protein, decreased hippocampal volume, and weaker network connections are apparent in the brain, but memory symptoms assessed by paper and pencil tests have not yet appeared. Performance tests of complex daily tasks may be more sensitive and detect early functional impairment. METHODS/STUDY POPULATION: This is a cross-sectional analysis of an ongoing cohort study. Cognitively normal (CN) older adults completed 3 standardized complex daily tasks from the Performance Assessment of Self-Care Skills (PASS) in their home. Biomarkers of AD were assessed within 2-3 years of an individuals completion of the PASS and include: amyloid accumulation, hippocampal volume, and resting-state functional connectivity (rs-fc) signature. Associations between performance on PASS tasks and the biomarkers of AD were quantified by Pearson point-biserial correlations, as biomarker data was normally distributed and PASS scores fell between two categories (acceptable or optimal quality of performance). Correlations with a 95% confidence interval (CI) that did not include 0 were considered significant. RESULTS/ANTICIPATED RESULTS: 161 CN participants (mean age 74.3 years, 55% female) were included. Mean score on the 3 PASS tasks ranged from 2.67 [standard deviation (SD): .47] to 2.90 (SD: .16) out of 3. Mean amyloid PET on Centiloid scale was 23.8 (SD: 34.8); mean partial volume corrected hippocampal volume was 7448.5 (SD: 909.8); mean rs-fc signature was .805 (SD: .164). After controlling for age and gender, worse performance of complex daily activities was associated with smaller hippocampal volumes (Pearsons r: 0.302, p=.02, 95% CI: .179 to .416) and weaker rs-fc network connections (Pearsons r: 0.276, p=.03, 95% CI: .078 to .453), but not amyloid accumulation. DISCUSSION/SIGNIFICANCE: This study suggests that worse performance of complex daily tasks may be associated with markers of neurodegeneration. These findings could lead to a better understanding of functional changes that may occur during the preclinical stage of AD.